The Implementation of Problem Based Instruction Model to Improve Problem Solving Ability on Mechanical Wave Material at SMA Negeri 3 Banda Aceh - Sri Suryawati (Asian Journal of Science Education, 2021)
The research objectives were (1) to determine the increase in problem-solving abilities using the problem-based instruction model for class XI-MIPA-7 students on mechanical wave material at SMA Negeri 3 Banda Aceh, (2) to describe the activities of teachers and students in learning mechanical wave material using the problem-based instruction model for class XI-MIPA-7 SMA Negeri 3 Banda Aceh, and (3) to find out the response of XI-MIPA-7 students of SMA Negeri 3 Banda Aceh after using the problem-based instruction model. This study used a classroom action research method. The research subjects were 34 students of XI-MIPA-7 SMA Negeri 3 Banda Aceh. Data analysis using percentage techniques. Based on the results of data analysis, it can be concluded as follows: (a) there is an increase in student learning outcomes in solving problems by applying the problem-based instruction model. The class average score in cycle 1 meeting 1 was 71.47 with 58.2% completeness, while in cycle 1 meeting 2 increased to 82.5 with completeness 82.35%. And in cycle II the class average value is 85 with completeness of 94.11%; (b) teacher and student activities have increased in each cycle, an increase in the ability of teachers to manage to learn from moderate to very good categories, and (c) student responses tend to be positive. So, it can be said that the problem-based instruction model can be used to improve the ability to solve mechanical wave material problems in class XI-MIPA-7 at SMA Negeri 3 Banda Aceh.